An Interconnected Wind Driven SEIG System Using SVPWM Controlled TL Z-Source Inverter Strategy for Off-Shore WECS - Ajin Sekhar CS; V. Raghavendrarajan; R. Hemantha Kumar; M. Sasikumar (IAES Indonesian Section, 2013)
This paper discuss about the interconnection of wind driven SEIG for drive applications by using TL Z-source inverter strategy .TL Z-source consists of two coupled inductors having turns ratio γTL and four diodes are used . The wind energy system uses a two Self Excited Induction generator (SEIG) connected parallel in order to increase the reliability. The proposed system components like wind turbine SEIG, rectifier, SVM Controlled TL Z-source inverter, are modeled by matlab Simulink. The maximum power can be extracted and supplied to the load efficiently by using TL Z-source inverter with a proper value of modulation index. The simulation output is analysed experimentally using 500 W experimental setup.